Factors affecting financial sustainability of water and sewerage provision in Cape Town, South Africa - Beda, M (Annals of Spiru Haret University. Economic Series, 2021)
Financial sustainability of water and sewerage provision is undermined by consumers’ inability and reluctance to pay service fees. South African municipalities are providing water and sewerage services at high maintenance and operational costs, households and businesses that are unable and/or committing to pay their full accounts timeously. This study examines the provision of water and sewage service and presents strategic framework to manage revenue collection to achieve financial sustainability of water and sewerage provision. The study applied the interpretive research method to collect and analyzed data for improved understanding of service provision and revenue collection mantra. The main objective of this study was to investigate factors affecting financial sustainability of water and sewerage provision in Cape Town. In this study an interpretive research method was embraced and qualitative research design was used to collect qualitative data by means of interviewing the senior officials using semi structured interviews. Narrative methods of analysis were applied in analyzing data collected from randomly selected Cape Town officials including observations and secondary data. The results showed that although Cape Town is making efforts of generating revenue by means of enforcing water and sanitation services payments, there is still a percentage of residents that refuses to pay for services resulting in revenue loss. The other reason for loss of revenue was unaccounted water which was the focus of Water and Sanitation. The reasons advanced for unwillingness to pay for water and sanitation services by consumers were unemployment, poverty, unequal distribution of services and general ignorance.